1998
DOI: 10.1086/305689
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Dense Stellar Clusters against Relativistic Collapse. II. Maxwellian Distribution Functions with Different Cutoff Parameters

Abstract: We investigate the stability of dense stellar clusters against relativistic collapse by approximate methods described in the previous paper in this series. These methods, together with the analysis of the fractional binding energy of the system, have been applied to sequences of equilibrium models, with cuto † in the distribution function, which generalize those studied by Zeldovich & Podurets. We show the existence of extreme conÐgurations, which are stable all the way up to inÐnite values of the central reds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…The 2D map of the binding energy was constructed by applying a bicubic spline interpolator to the model points. The models nicely cover the first maximum of f , where dynamical instability is expected to set in (Bisnovatyi-Kogan et al 1998;Bisnovatyi-Kogan & Merafina 2006).…”
Section: Binding Energymentioning
confidence: 83%
See 2 more Smart Citations
“…The 2D map of the binding energy was constructed by applying a bicubic spline interpolator to the model points. The models nicely cover the first maximum of f , where dynamical instability is expected to set in (Bisnovatyi-Kogan et al 1998;Bisnovatyi-Kogan & Merafina 2006).…”
Section: Binding Energymentioning
confidence: 83%
“…To the right of the white dot are models with deeper potential wells and correspondingly higher central redshifts. This situation is reminiscent to that of the family of models discussed by Bisnovatyi-Kogan et al (1998) which also exhibits both bifurcations (i.e. more than one solution for a given set of model parameters) and limiting values for a parameter connected to the energy at the outer boundary.…”
Section: Existence Of Solutionsmentioning
confidence: 88%
See 1 more Smart Citation
“…Different values of these parameters give a two-dimensional family of equilibrium solutions. The set of solutions forρ Λ = 0 at different values of W 0 was obtained by Bisnovatyi-Kogan et al (1998). We solved numerically the Poisson equation for gravitational equilibrium at different values of the two parameters (W 0 ,ρ Λ ) mentioned above.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Bisnovatyi- Kogan et al (1998) found the set of solutions at Λ = 0 forM(ρ m0 ) andM(α) curves in the Newtonian case. These curves are shown in Figs.…”
Section: Numerical Resultsmentioning
confidence: 99%